2022
DOI: 10.3390/cancers14061406
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis Inhibitors and Immunomodulation in Renal Cell Cancers: The Past, Present, and Future

Abstract: Angiogenesis inhibitors have been adopted into the standard armamentarium of therapies for advanced-stage renal cell carcinomas (RCC), but more recently, combination regimens with immune checkpoint inhibitors have demonstrated better outcomes. Despite this, the majority of affected patients still eventually experience progressive disease due to therapeutic resistance mechanisms, and there remains a need to develop novel therapeutic strategies. This article will review the synergistic mechanisms behind angiogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 123 publications
0
17
0
Order By: Relevance
“…Asterisk represents significant differential ECAR value between LRNF1 overexpression group and negative control group, as well as between LRNF1 overexpression group and LRFN1 + mimics group using unpaired t test (P < 0.05). *P < 0.05; ***P < 0.001; ****P < 0.0001 from different perspectives will help to deepen the understanding of the interaction between tumor cells and TME, thereby improving the overall efficacy of renal cancer treatment [44,45]. Considering that a large number of lymphocyte infiltration led by CD8 + T cells and the general increase of immune checkpoint molecules are in the LRFN1 high group, and this phenomenon is specific in RCC, this study demonstrated that LRNF1 may affect glycolytic effects of ccRCC cells to evade immune surveillance [46], and thus mediating the immune-infiltrating TIME in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Asterisk represents significant differential ECAR value between LRNF1 overexpression group and negative control group, as well as between LRNF1 overexpression group and LRFN1 + mimics group using unpaired t test (P < 0.05). *P < 0.05; ***P < 0.001; ****P < 0.0001 from different perspectives will help to deepen the understanding of the interaction between tumor cells and TME, thereby improving the overall efficacy of renal cancer treatment [44,45]. Considering that a large number of lymphocyte infiltration led by CD8 + T cells and the general increase of immune checkpoint molecules are in the LRFN1 high group, and this phenomenon is specific in RCC, this study demonstrated that LRNF1 may affect glycolytic effects of ccRCC cells to evade immune surveillance [46], and thus mediating the immune-infiltrating TIME in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, renal cancer is also one of the most immunogenic cancers with a tumour microenvironment (TME) characterized by an infiltration of various immune cells with an immunosuppressive phenotype [ 11 ]. Considering the link between angiogenesis and anti-tumour immunity, there is a strong rationale to combine ICI (anti-PD-1) with anti-angiogenic TKI [ 12 ]. Four combinations are currently approved for first-line treatment in m ccRCC (3 TKI-ICI-axitinib plus pembrolizumab, cabozantinib plus nivolumab and lenvatinib plus pembrolizumab—and 1 ICI-ICI-nivolumab plus ipilimumab) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Renal cell carcinoma (RCC) is one of the fastest-growing malignancies worldwide and has more than doubled its incidence in the past decades [ 1 ]. It is the ninth most common malignancy and accounts for more than 13,000 deaths in the United States annually [ 1 , 2 ]. Since 2015, immune checkpoint inhibitors (ICIs) have changed the therapeutic landscape of RCC [ 3 ].…”
Section: Introductionmentioning
confidence: 99%